APLIKASI METODE GEOMAGNET DALAM EKSPLORASI PANASBUMI - Sudaryo Broto (Diponegoro University, 2011)
Geophysics is a part of earth science that studies the Earth using the rules or principles of physics. Geophysicalmethods are divided into several methods, namely: gravity method, geomagnet, seismic, geoelectric andgeoradar.Geothermal energy is stored in the form of hot water or steam at a certain geological conditions at depth.Geothermal system is an area of geothermal or geothermal field is an area on the surface of the earth within acertain limit where there is geothermal energy in a certain rock hydrology. Geothermal manifestations consistof: ground hot, steaming ground, hot tubs, hot mud pools, hot springs, fumaroles, geysers, silica sinter.Fault is a fracture rock mass shift relative one part against another. Fault structure is associated withgeothermal manifestations, because the manifestations that came out to the surface because of the fault beneaththe surface.From the results of investigations in the area geomagnet Jaboi, magnetic anomalies were divided into three,namely anomaly is very low with values between -600s/d200 nT anomaly as strongly altered rock and weatheredrock; low anomaly with values> -200s/d300 nT as alluvial and pyroclastic rocks ; high anomaly with valuesbetween> 300s/d700 nT as a rock rhiolit / dacite volcanic and fresh. Geothermal potential area is the area oflow magnetic anomaly values in the presence of manifestations of hot water and is controlled by the fault.